SURFACE-COMPOSITION OF MIXED SURFACTANT MONOLAYERS AT CONCENTRATIONS WELL IN EXCESS OF THE CRITICAL MICELLE CONCENTRATION - A NEUTRON-SCATTERING STUDY - Staples, E; Thompson, L; Tucker, I; Penfold, J; Thomas, R; Lu, J (1993)
Spectra neutron reflection has been used to determine the adsorption of sodium dodecyl sulfate (SDS) and n-dodecyl triethylene glycol (C12E3) at the air-solution interface at a fixed bulk composition ratio (65 mol % C12E3) over a wide range of concentrations in excess of the critical micelle concentration. The results are compared with those obtained from the application of regular solution theory to surface tension data for the same system. The proportion of SDS in the absorbed layer is in good agreement with the theoretical predictions.